Carpaccio’s Original Painting Installation in the Scuola Dalmata: Where and Why - Piovan, Valentina; Randazzo, Stefania; Conn, Melissa (Confraternitas)

(untitled) (Iter Press, 2021)
The original installation of Vittore Carpaccio’s narrative paintings in the Scuola Dalmata has long been assumed to have been in the upper chapter hall, following the practice used in other Venetian confraternities (Scuole). Studies and observations during the recent conservation campaign of the canvases have led to a new hypothesis that Carpaccio may very well have instead placed his paintings on the ground floor, as we see them today, due to a heated dispute with the Priory of the Order of Saint John of Jerusalem over the control of the upstairs premises.